1986
DOI: 10.1016/0014-5793(86)81426-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium induces cyclic GMP formation in Dictyostelium

Abstract: Cyclic GMP is rapidly formed a few seconds after binding of chemotactic signailing molecules to specific receptors on the cell surface of Dictyostelium amoebae. This phenomenon could be mimicked by addition of a pulse of Ca2+ to ~~eabili~d amoebae. The con~ntration of Ca 2+ for haIf-maximal response was 60 FM. Other ions (K+, Na+, Mg*+ or Mn2+) had no effect. A pulse of 5 PM IP, produced a cyclic GMP response of similar magnitude but IP, elicited no response. The data provide strong support for the hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…However, because 8-CPT-cAMP induces a normal cGMP response, this may, at saturating concentrations, suffice to induce some chemotaxis, perhaps due to enhanced cytokinesis. (49,50). Remarkably, the cGMP response induced by 8-CPT-cAMP reaches much higher levels than that induced by cAMP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, because 8-CPT-cAMP induces a normal cGMP response, this may, at saturating concentrations, suffice to induce some chemotaxis, perhaps due to enhanced cytokinesis. (49,50). Remarkably, the cGMP response induced by 8-CPT-cAMP reaches much higher levels than that induced by cAMP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that Lit inhibits Ins(1 ,4,5)P3 accumulation, but stimulates guanylyl-cyclase activation contradicts an earlier hypothesis that guanylyl cyclase is activated via the Ins(1 ,4,5)P3/Ca2 + pathway (Europe-Finner andNewell, 1985, 1986;Small et al, 1986;Snaar-Jagalska et al, 1988~). Further evidence against this mechanism are observations that submicromolar Ca2 + concentrations completely inhibit guanylyl-cyclase activity in vitro (Janssens et al, 1989) and that a partial cAMP antagonist, which cannot increase Ins(1 ,4,5)P3 levels, nevertheless induces normal cGMP accumulation (Peters et al, 1991).…”
Section: Discussionmentioning
confidence: 82%
“…Figure 5 shows the kinetics of the changes in the numberof actin foci after stimulation. The number of filaments of myosin II increased on the cell membrane 25-35 sec after the start of stimulation (Fig. 4h).…”
Section: Resultsmentioning
confidence: 88%
“…However, the observation that normal responses of myosin II occurred in the presence of EGTA,LaCl3, and ruthenium red rules out the possibility that increases in levels of Ca2+ ions from the extracellular environmentinduce the reorganization of myosin II. Europe-Finner and Newell (7) reported that inositol (25). Moreover, CGMP induces the CAMP-stimulated uptake of Ca2+ ions (18).…”
Section: Discussionmentioning
confidence: 99%